Effects of Growth Medium and Water Stress on Soybean [Glycine max (L.) Merr.] Growth, Soil Water Extraction and Rooting Profiles by Depth in 1-m Rooting Columns - Gebre, Michael Gebretsadik; Earl, Hugh James (Frontiers in Plant Science, 2020)
The pattern of soil water availability in frequently watered small pots is different from field environments. In small pots, volumetric soil water content (VSWC) is relatively high throughout the rooting zone due to a lack of suction to remove water from large and midsize capillaries. This necessitates the use of growing media with large pore space to avoid anaerobic conditions and so prohibits the use of field soil (FS) in small pots. However, in 1-m rooting columns, the 0.01-MPa gravitational potential difference between top and bottom might permit the use of lightly-amended FS as a growing medium and provide for realistic VSWC and rooting profiles by depth. This study aimed to investigate the effects of amending a typical sand-based potting mix with different amounts of FS on soybean growth [dry matter (DM) accumulation], water use, VSWC and rooting profiles by depth under control and water stress conditions, in 1-m rooting columns (polyvinyl chloride tubes having an inside diameter of 10 cm and length of 1 m). We tested three soil types (0%, 50%, and 67% FS mix), watered to 100% of the maximum soil water holding capacity (SWHC; control) or 75% SWHC (stress). VSWC was calculated from time-domain reflectometry measurements. Compared to all soil types, the 67% FS mix resulted in the highest DM accumulation, water use, water use efficiency (WUE), and also produced realistic VSWC and rooting profiles by depth similar to those reported in the literature under field conditions. The water stress treatment reduced shoot, root, whole-plant DM, and water use, by 24, 13, 22 and 25%, respectively, but increased root to shoot ratio and WUE by 18 and 6%. Of the three soil types tested, the 67% FS mix was the most suitable growth medium for controlled environment studies of root functional traits affecting drought tolerance in soybean. This study provides novel phenotyping tools to select for root function and yield formation traits that could increase soybean yield under soil water deficit conditions.